2014
DOI: 10.1227/neu.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Foraminotomy Through Tubular Retractors via a Contralateral Approach in Patients With Unilateral Radiculopathy

Abstract: A minimally invasive, facet-sparing contralateral approach is an effective technique for treatment of radiculopathy due to foraminal compression. It also allows for decompression of lumbar spinal stenosis and bilateral lateral recess decompression without the need for fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“… 2) Several studies with low revision rates after decompression-alone procedure included many fewer cases with L5/S LFS than the present study. 6 , 18 , 19) The dorsal root ganglion/foraminal height ratio becomes maximum at the intraforaminal area of L5/S, 20) as the mobility of L5 nerve root is limited by a large L5/S facet joint, iliolumbar ligament, and sacral ala in the extraforaminal area. 21 , 22) These anatomical features increase the incidence of symptomatic LFS at L5/S as well as the recurrence rate after MFD.…”
Section: Discussionmentioning
confidence: 99%
“… 2) Several studies with low revision rates after decompression-alone procedure included many fewer cases with L5/S LFS than the present study. 6 , 18 , 19) The dorsal root ganglion/foraminal height ratio becomes maximum at the intraforaminal area of L5/S, 20) as the mobility of L5 nerve root is limited by a large L5/S facet joint, iliolumbar ligament, and sacral ala in the extraforaminal area. 21 , 22) These anatomical features increase the incidence of symptomatic LFS at L5/S as well as the recurrence rate after MFD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases where central stenosis is associated with significant and symptomatic unilateral foraminal stenosis, a contralateral approach may be preferable because it affords excellent visualization of the contralateral foramen [44].…”
Section: Discussion Backgroundmentioning
confidence: 99%
“…Alimi et al 40 reported the results of a unilateral minimally invasive lumbar foraminotomy through tubular retractors via a contralateral epidural approach for unilaterally dominant radiculopathy arising as a consequence of root compression. In a 12 month follow up of 32 patients they reported excellent functional outcome in 95% with one patient requiring revision by fusion.…”
Section: Discussionmentioning
confidence: 99%